EcoHealth manual - Unahalekhaka, A.; Pichpol, D.; Meeyam, T.; Chotinun, S.; Robert, G.L.; Robert, C.S. (Chiang Mai University, 2013)
Feeding the growing population, while promoting better health, environment and sustainable livelihood opportunities is a global challenge that we all share. EcoHelath is an approach that addresses some of these challenges by assuring better health for people, animals and environment. The IDRC supported program EcoZEID (Ecosystem Approaches to Better Management of Zoonotic Emerging Infectious Diseases) is being implemented by International Livestock Research Institute (ILRI) since 2009, in five countries in South East Asia. The project worked with a large number of regional stakeholders to capacitate them in understanding and incorporating/ practicing EcoHealth. Two EcoHealth resource centres have been setup at leading universities in Indonesia (Gadjah Mada University) and Thailand (Chiang Mai University) as part of the project. This manual was prepared as a resource for teaching EcoHealth concepts to university students from diverse disciplines. It is intended to introduce examples of important aspects of EcoHealth, providing real world examples of each aspect and suggesting how the EcoHealth approach to research can be applied to improve the quality of human health, animal health and the environment. The EcoHealth approach involves interdisciplinary efforts: experts from various academic fields working as a team, learning to speak each other’s language, with the strengths of each discipline actively supporting each other. Moreover EcoHealth encourages researches to consider the broadest context when looking at concrete problems. That transdisciplinary approach can be employed by users of this manual. Individuals with a strong academic background in one area, e.g., the social sciences, can provide help to others who have had less experience in that discipline. By building an understanding of the concepts and research methods used by other fields, students can cooperatively develop their capacity to effectively apply the EcoHealth approach as members of interdisciplinary research teams.